Alignment techniques for DRAGON-I LIA - 代志勇 谢宇彤 李洪 章文卫 刘云龙 潘海峰 章林文 邓建军 (Chinese physics C, 2009)
DRAGON-I designed and manufactured by CAEP is a linear induction accelerator which can produce a 20 MeV-3 kA-60 ns electron beam. The high performance required for the machine is determined by the beam quality and thus is greatly dependent on the accelerator alignment. In order to reduce the chromatic effect of the beam, the stretched wire technique has been developed to measure magnetic axes of the cells precisely, and the dipole steering magnets have been equipped into each cell to correct its magnetic axis misalignment. Finally, the laser tracker has been used to examine the installation error of the accelerator. In this paper, different alignment techniques and the primary results are presented and discussed.